Aplikasi ZPT Atonik pada Berbagai Konsentrasi terhadap Pertumbuhan dan Perkembangan Buah Jambu Madu Deli Hijau (Syzygium aqueum) - Fikri , Mu’ammar; Juhan , Muhammad (JURNAL AGROPLANT, 2021)
Honey water guava (Syzygium aqueum) is a new fruit variety, but not many have cultivated it. This guava comes from the Myrtaceae family which has 3 varieties, the shape of the fruit is like a bell with a reddish green skin color, the taste is sweet like honey. This study aims to describe the growth and development of green deli honey guava fruit at different atonic concentrations and to obtain the best concentration. This research was conducted in Pancakarya Village, Ajung District, Jember Regency, in November 2020 - January 2021, with an altitude of 50 m above sea level. This study used a non-factorial randomized block design (RAK), with 6 treatments, repeated 4 times, a total of 24 research objects. The treatments studied were F0 = Control, F1 = 20 ml/L, F2 = 40 ml/L, F3 = 60 ml/L, F4 = 80 ml/L, F5 = 100 ml/L. Data were analyzed by means of variance (Anova), if significantly different, followed by a 1% BNT test. The results showed that the Atonic concentration of F3 treatment (60 ml/L) gave optimal results on diameter, length, unit weight and fruit sugar content. And not significantly different to the parameters of the resistance of the stump and the overall weight of the fruit This research should be carried out during the dry season, so that PGR can be absorbed maximally by the fruit.